2016
DOI: 10.1113/jp272235
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training in the treatment of non‐alcoholic fatty liver disease related fibrosis

Abstract: The incidence of non-alcoholic steatohepatitis (NASH) is rising but the efficacy of lifestyle modifications to improve NASH-related outcomes remain unclear. We hypothesized that a western diet (WD) would induce NASH in the Otsuka Long-Evans Tokushima Fatty (OLETF) rat and that lifestyle modification would improve this condition. Eight-week-old Long-Evans Tokushima Otsuka (L) and OLETF (O) rats consumed a control diet (10% kcal fat, 3.5% sucrose) or a WD (45% kcal fat, 17% sucrose, 1% cholesterol) for 24 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 54 publications
(135 reference statements)
2
48
1
Order By: Relevance
“…; Linden et al . ). Inappropriate cholesterol metabolism has received considerable attention in human and animal studies of NAFLD, and has been observed to modulate multiple pathways triggering NASH development (Min et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Linden et al . ). Inappropriate cholesterol metabolism has received considerable attention in human and animal studies of NAFLD, and has been observed to modulate multiple pathways triggering NASH development (Min et al .…”
Section: Introductionmentioning
confidence: 97%
“…High calorie, high fat diets (HFD) are associated with NAFLD risk and obesity in humans and are commonly utilized to induce hepatic steatosis in rodent models. However, chronic HFD-induced hepatic steatosis does not progress to non-alcoholic steatohepatitis (NASH) in rodent models (Matteoni et al 1999), whereas we and others have shown that the addition of refined sugar and/or cholesterol to an HFD induces NASH-like outcomes (Gan et al 2014;Bashiri et al 2016;Linden et al 2016). Inappropriate cholesterol metabolism has received considerable attention in human and animal studies of NAFLD, and has been observed to modulate multiple pathways triggering NASH development (Min et al 2012;Arguello et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Due to the high rates of individuals with hepatic fat accumulation, pharmaceutical, and nutritional strategies were developed to curb the damage of this disorder. Physical exercise has been extensively recommended for providing relevant actions in the battle against hepatic fat accumulation and metabolic disorders …”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise has been extensively recommended for providing relevant actions in the battle against hepatic fat accumulation and metabolic disorders. [5][6][7][8][9] Different studies have elucidated the molecular pathways involved in the obesity-induced hepatic fat accumulation. Recently, Tabata et al 10 described the effects of the Cdc2-like kinase (CLK2) on the suppression of fatty acid oxidation and hepatic ketogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the present study, where central adiposity was seen in concert with early liver injury and portal fibrosis in DDOST+/-mice fed a high AGE diet. Whether reiterates the complexity of the relationship between metabolic factors and liver injury, given that exercise is a feasible intervention to improve liver fibrosis in patients with NAFLD 217 and relates to adiposity in NAFLD 218 .…”
Section: Discussionmentioning
confidence: 99%